CROSS-CULTURAL ASPECTS OF METAPHORICAL FRAMING IN POLITICAL DISCOURSE - T. V. Andryukhina (Vestnik MGIMO-Universiteta)
The article examines cross-cultural aspects of metaphorical framing in political discourse. The author notes the importance of conceptual metaphor in framing the conceptual domain of politics, political discourse as a whole, its perception as well as political reality itself. The author shares an opinion that the metaphorical structure of basic concepts of a nation always correlates with its fundamental cultural values. However, the examination of political discourse from the cross-cultural perspective reveals the cases of metaphor uses that don't meet the requirements of cultural coherence and may lead to negative cognitive and communicative consequences. Along with admitting a wide discrepancy between metaphorical models in western and oriental political discourse, the author gives some examples of metaphorical coherence as well as its violation in a number of basic metaphors in American, British and Russian political discourse. To illustrate how cross-cultural factors determine the specific character of metaphorical framing, the article analyses the dynamic character of metaphorical models that can realize diverse scenarios in different national varieties of political discourse. An observation is made about the dependence of metaphoric scenarios in different national varieties of political discourse on the cultural, historical, social and political components of the national cultural cognitive map. The latter is heterogeneous as it is structured by the objectified individual, group, and national verbal and nonverbal experience. This explains, for instance, why there are examples of similarity as well as discrepancy between metaphorical framing in ideologically different party varieties of political discourse within the national political discourse as well as in the rhetoric of politicians belonging to different generations. The observations are illustrated by cross-linguistic data proving the dynamic character of metaphorical models, their variability and potential for conveying new meaning nuances that reflect culture-specific characteristics of the political situation in discourse.